The relationship between technical vocabulary breadth, english language proficiency, and vocabulary learning strategies among engineering undergraduates at Universiti Malaysia Pahang - Amri Muaz, Azmimurad (2019)
English for Specific Purposes (ESP) is designed to appeal to learners learning languages in specific disciplines. ESP deals with words that are designed precisely or has its own meaning in specific fields. As engineering students read texts with technical terms that have a specific meaning in the engineering field, the vocabulary knowledge of technical terms is important for them to comprehend the texts. However, engineering students were found to face problems whenever they encounter texts containing technical terms. Hence, this study aims to investigate the vocabulary breadth of technical vocabulary among engineering students at Universiti Malaysia Pahang. This study employs mixed method explanatory design which seeks to explore the relationship between technical vocabulary breadth, English language proficiency and vocabulary learning strategies. A vocabulary test which is a word meaning test is used in this research along with a vocabulary learning strategies questionnaire and a semi-structured interview. The technical terms were taken from the Engineering English Word List (EEWL). The test was administered to 138 students majoring in engineering from five engineering faculties in their third and fourth year at Universiti Malaysia Pahang. The findings showed that there was a moderate positive relationship was found between technical vocabulary breadth and language proficiency. It was also found that listening to and watching English media is the most preferred strategy to be used among engineering undergraduates in learning technical vocabulary. This study proves the issue in which university students, especially engineering students are facing problem with vocabulary mastery. The current research recommends further research to be done in helping the students to improve their vocabulary breadth on technical terms.